Dengue fever with hemorrhagic manifestations in travellers returning to Quebec from Asia - Duperval, Raymond (Pulsus Group Inc, 1993)
Two cases of dengue fever with hemorrhagic manifestations were observed in 1990 and 1992 among travellers returning from Asia, while a third presented with classical dengue fever after the patient’s first trip to an endemic region. All experienced rash, thrombocytopenia and coagulation disorders and had flavivirus serology consistent with exposure to dengue virus.